Synergistic hydrolysis of filter paper by recombinant cellulase cocktails leveraging a key cellobiase, Cba2, of Cellulomonas biazotea - SIDDIQUE, Faiza; Hon LAM, Edward Kat; Raymond WONG, Wan Keung (Frontiers in Bioengineering and Biotechnology, 2022)
Cellulomonas biazotea, a Gram-positive cellulolytic bacterium isolated from soil, is capable of producing a complete cellulase complex exhibiting endoglucanase, exoglucanase, and cellobiase activities. Despite the presence of a full complement of all three types of cellulases, samples prepared from both cell lysates and culture media of C. biazotea showed only weak synergistic activities formed among the cellulase components, as reflected by their inefficient performance in filter paper hydrolysis. However, when the 5 previously characterized recombinant cellobiases of C. biazotea were mixed individually or in different combinations with recombinant enzyme preparations (CenA/Cex) containing an endoglucanase, CenA, and an exoglucanase, Cex, of another Cellulomonas species, C. fimi, the cellulase cocktails exhibited not only much higher but also synergistic activities in filter paper hydrolysis. Among the 5 C. biazotea cellobiases studied, Cba2 was shown to perform 2.8 to 3.8 times better than other homologous isozymes when acting individually with CenA/Cex. More noteworthy is that when Cba2 and Cba4 were added together to the reaction mixture, an even better synergistic effect was achieved. The filter paper activities resulting from Cba2 and Cba4 interacting with CenA/Cex are comparable to those obtained from some commercial fungal cellulase mixtures. To our knowledge, our results represent the first demonstration of synergistic effects on filter paper hydrolysis achieved using recombinant bacterial cellulases.